2010
DOI: 10.1177/0734904110386188
|View full text |Cite
|
Sign up to set email alerts
|

Thermocouple Response in Fires, Part 2: Validation of Virtual Thermocouple Model for Fire Codes

Abstract: A virtual thermocouple model for high fidelity multiphysics computer simulation is introduced in this article. Detailed thermocouple and gas temperature (Coherent Anti-Stokes Raman Scattering) measurements were performed using a well-controlled, adiabatic, flat-flame Hencken burner, which provided data for validating the thermocouple model in a Sandia National Laboratories fire code. Comparison of simulation results to test data indicated a mean error of 6% between the thermocouple reading and predicted temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…1a) in case of = 1. The value 0.2 was accepted as minimum because in practice of thermocouple maintenance even in case of the long operation terms and mechanical damages the lowering of to such values is improbable [1][2][3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) in case of = 1. The value 0.2 was accepted as minimum because in practice of thermocouple maintenance even in case of the long operation terms and mechanical damages the lowering of to such values is improbable [1][2][3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, temperature measurements are used for control and condition monitoring of technological equipment and quality of technological process behavior in all industries. Such as [1][2][3][4] metallurgy, power engineering, aircraft industry, and also medicine, fire safety [5,6] and other person focus areas are among such productions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, CARS measurements also showed that Hencken burners are nearly adiabatic. 3,4 The grid was generated using polyhedral cell elements to create a conformal multiregion to allow heat transfer between solids and fluids. Figure 3 shows the grid and the detailed thermocouple surrounded by boundary-layer prism cells.…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…The virtual thermocouple model in Vulcan and experimental validation based on well-established flame experiments, using a Hencken burner, various sizes of thermocouples, and Coherent Anti-Stokes Raman Spectroscopy (CARS), are discussed in detail for MIMS thermocouples. 3,4 To supplement these earlier research investigations, detailed multiphysics modeling 5 was performed using a commercial code STAR-CCM + . 6 Although Vulcan and STAR-CCM + have similar physical modeling capabilities, the commercial code has more versatile meshing capabilities, which is an advantage when complex, multiregion grids are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual thermocouples are treated as truncated cylinders with hemispherical end closures that are exposed to fires. 8,9 It is capable of modeling combustion, soot, and thermal radiation and has been validated for various fire situations. 10,11 Although it exhibits strengths in the case of the modeling of actual fire scenarios, it assumes infinitely long thermocouples and its meshing capabilities limit its use in various applications.…”
Section: Introductionmentioning
confidence: 99%